2017
DOI: 10.1002/chem.201605294
|View full text |Cite
|
Sign up to set email alerts
|

Anatase TiO2 Mesocrystals: Green Synthesis, In Situ Conversion to Porous Single Crystals, and Self‐Doping Ti3+ for Enhanced Visible Light Driven Photocatalytic Removal of NO

Abstract: Mesocrystals are of great interest for a wide range of applications owing to their unique structural features and properties. The realization of well-defined metal oxide mesocrystals through a facile and green synthetic approach still remains a great challenge. Here, a novel synthesis strategy is reported for the production of spindle-shaped anatase TiO mesocrystals with a single-crystal-like structure, which was simply achieved through the one-step hydrolysis reaction of TiCl in the green and recyclable media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 70 publications
(183 reference statements)
5
39
0
Order By: Relevance
“…The 68.3° angle between the (002) and (101) planes in the SAED pattern of Figure b proves that the nanocrystals align along the [001] direction to form an ordered assembly, and the regular single‐crystal‐like SAED pattern suggests the formation of mesocrystals . Furthermore, the light‐colored regions in Figure b indicate the presence of pores of approximately 3.4 nm in size between the nanocrystals in the individual particle; this further proves the mesoporous characteristics of the mesocrystal . In addition, the HRTEM image in Figure c clearly reveals that the crystal lattice of the nanoparticles is highly parallel, which is a characteristic of mesocrystals .…”
Section: Resultssupporting
confidence: 88%
“…The 68.3° angle between the (002) and (101) planes in the SAED pattern of Figure b proves that the nanocrystals align along the [001] direction to form an ordered assembly, and the regular single‐crystal‐like SAED pattern suggests the formation of mesocrystals . Furthermore, the light‐colored regions in Figure b indicate the presence of pores of approximately 3.4 nm in size between the nanocrystals in the individual particle; this further proves the mesoporous characteristics of the mesocrystal . In addition, the HRTEM image in Figure c clearly reveals that the crystal lattice of the nanoparticles is highly parallel, which is a characteristic of mesocrystals .…”
Section: Resultssupporting
confidence: 88%
“…The corresponding high‐resolution Ti 2p, O 1s, C 1s, and N 1s spectra of the DTMCs, g‐C 3 N 4 NSs, and 33.3 % g‐C 3 N 4 /DTMCs were then compared meticulously to gain a deep insight into the interaction between the DTMCs and g‐C 3 N 4 NSs after coupling. As illustrated in Figure a, only two major peaks centered at 458.8 and 464.5 eV are observed in the Ti 2p spectrum of the DTMCs, which can be assigned to the Ti 4+ 2p 3/2 and Ti 4+ 2p 1/2 peaks of TiO 2 , thereby confirming the absence of Ti 3+ on the surface of the sample . These two peaks are slightly shifted to the lower binding energies of 458.7 and 464.4 eV after coupling of the DTMCs with the g‐C 3 N 4 NSs.…”
Section: Resultssupporting
confidence: 54%
“…Recently, it was demonstrated that the photocatalytic performance of TiO 2 could be enhanced by fabricating mesocrystalline architectures, as these kinds of oriented superstructures arranged by TiO 2 nanocrystal building blocks possess effective conduction pathways and remarkably long‐lived charges . Subsequent studies revealed that the further introduction of Ti 3+ and oxygen vacancies (Ov) into mesocrystalline TiO 2 architectures could broaden the absorption spectrum of TiO 2 to the visible‐light region, thereby making the resultant defective TiO 2− x mesocrystals visible‐light responsive without introducing recombination centers for the photogenerated charge carriers . Accordingly, the realization of defective TiO 2− x mesocrystals (containing Ti 3+ or Ov) would lead to improved photocatalysis as a result of the synergistic effects of stronger light‐harvesting ability and improved charge‐separation efficiency of the photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesocrystals also permit the advantages of single crystals as well as large surface area, making them more promising in the applications of catalysis, sensing and energy storage and conversion . In our and other group's previous work, TiO 2 mesocrystals with different phase and morphology were synthesized, which exhibited superior performance in energy storage and conversion, sensing and photocatalysis . However, TiO 2 mesocrystals with tunable microporous structure have not been reported, which could be a robust structure allowing promising application in catalysis.…”
Section: Introductionmentioning
confidence: 91%